The Effectiveness of Project and Presentation Types of Cooperative Learning Model on Social Studies Concept Understanding of Elementary School Students - Mulyani, Srie; Suhaedah, Suhaedah; Caturiasari, Jennyta; Rizkita, Dilla (International Conference on Elementary Education, 2021)
Research was conducted to describe the results of student learning through a problem-solving model. Sampling was done by one group pretest-posttest design. The type of research used is the pre- experiment with the form of the design of one group pretest-posttest with research subjects of grade students in one of the public elementary schools. Subject retrieval using single subject and subject number four students. The research data were obtained using test descriptions and observations. Based on the analysis results, the project model and presentation gave a enhance. These results were seen based on the N-Gain test by 0.86 in high categories. Subjects are 6 students of class IV. Data analysis techniques by observing the development of n-gain. This study showed that student understanding of pretest is 53,75 point categorized as low and posttest is 93.00 point categorized as good. It means that cooperative learning projects and presentation models suitable for elementary school social studies learning and can encourage students to build an understanding of concepts. Construction of the concept through the process of connecting knowledge in solving learning problems.